Dirichlet problem for axisymmetric potential fields in a disk of the meridian plane. I - Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We develop new methods for the solution of boundary-value problems in the meridian plane of an antisymmetric potential solenoidal field with regard for the nature and specific features of axisymmetric problems. We determine the solutions of the Dirichlet problems for an axisymmetric potential and the Stokes flow function in a disk in an explicit form.